THE ROLE OF REGIONAL COOPERATION IN ENSURING THE ENVIRONMENTAL SAFETY OF CENTRAL ASIAN COUNTRIES - Prodanova, N. A.; Mukhtarova, K. S.; Baikushikova, G. A; Tursynbek, K. A. (Farabi Journal of Social Sciences, 2020)
Issues of environmental safety and sustainable development, including land degradation and soil pollution and efforts to combat these processes, are relevant for the region. At the beginning of the 21st century, new environmental security challenges are becoming even more relevant. A significant proportion of these challenges are global environmental problems. Security - the threat of land depletion and degradation, the huge unresolved complex water-energy problems, loss of the gene pool and biological diversity, other risks associated with ill-conceived and dangerous experiments in the field of creating new bio-environmental instruments. In these conditions, environmental safety becomes an integral part of the national security strategy of any state, and solutions environmental issues are turning into one of the core elements of any international integration association. The environmental policy of the countries of Central Asia is organized structurally and its main focus is the socio-economic and political process at the international level and within the state itself. The goal of countries' environmental safety policies is the environmental system of the environment and ensuring safety against threats that arise as a result of natural influences.